Generation of lentivirus-induced dendritic cells under GMP-compliant conditions for adaptive immune reconstitution against cytomegalovirus after stem cell transplantation - Sundarasetty, Bala Sai; Ruggiero, Eliana; Fronza, Raffaele; Schmidt, Manfred; Kalle, Christof von (Journal of translational medicine, 2015)
Background reactivation of latent viruses such as human cytomegalovirus (HCMV) after allogeneic hematopoietic stem cell transplantation (HSCT) results in high morbidity and mortality. Effective immunization against HCMV shortly after allo-HSCT is an unmet clinical need due to delayed adaptive T cell development. Donor-derived dendritic cells (DCs) have a critical participation in stimulation of naïve T cells and immune reconstitution, and therefore adoptive DC therapy could be used to protect patients after HSCT. However, previous methods for ex vivo generation of adoptive donor-derived DCs were complex and inconsistent, particularly regarding cell viability and potency after thawing. We have previously demonstrated in humanized mouse models of HSCT the proof-of-concept of a novel modality of lentivirus-induced DCs (“SmyleDCpp65”) that accelerated antigen-specific T cell development. Methods here we demonstrate the feasibility of good manufacturing practices (GMP) for production of donor-derived DCs consisting of monocytes from peripheral blood transduced with an integrase-defective lentiviral vector (IDLV, co-expressing GM-CSF, IFN-α and the cytomegalovirus antigen pp65) that were cryopreserved and thawed. Results upscaling and standardized production of one lot of IDLV and three lots of SmyleDCpp65 under GMP-compliant conditions were feasible. Analytical parameters for quality control of SmyleDCpp65 identity after thawing and potency after culture were defined. Cell recovery, uniformity, efficacy of gene transfer, purity and viability were high and consistent. SmyleDCpp65 showed only residual and polyclonal IDLV integration, unbiased to proto-oncogenic hot-spots. Stimulation of autologous T cells by GMP-grade SmyleDCpp65 was validated. Conclusion these results underscore further developments of this individualized donor-derived cell vaccine to accelerate immune reconstitution against HCMV after HSCT in clinical trials. Electronic supplementary material the online version of this article (doi:10.1186/s12967-015-0599-5) contains supplementary material, which is available to authorized users.
Gesehen am 23.02.2017